Determinants Of Interest Using Quick Response Indonesian Standard (Qris) - dulmen dulmen; abdul nasser hasibuan; Ali Hardana ali_hardana; arti damisa (Journal Of Sharia Banking, 2021)
There is a Quick Response Indonesian Standard (QRIS) application service provided by Indonesian banks to users to enable non-cash transactions via smartphones, but eighty-nine percent of Islamic banking students at IAIN Padangsidimpuan do not know, banking students should be the ones who better understand and at the same time as parties. So that the formulation of the problem and the purpose of the problem in this study is whether there is an influence of knowledge on interest in using QRIS, is there a beneficial effect on interest in using QRIS and is there a risk effect on interest in using QRIS and to find out whether there is an effect of knowledge on interest in using QRIS, to find out is there a beneficial effect on interest in using QRIS, and to find out whether there is an effect of risk on interest in using QRIS. The theory used in this study is about interest in knowledge, benefits, risks, and the Quick Response Indonesian Standard (QRIS). This research is a quantitative research. The data source used is primary data. The data collection technique used was a questionnaire with a sample size of 90 people. Data processing used SPSS version 24 software. The analysis techniques used were validity test, reliability test, normality test, linearity test, multi-linearity test, heteroscedasticity test, determination coefficient, partial (t) test and simultaneous (f) test and multiple linear regression analysis. . The results of the research test (t) indicate that the knowledge variable has a negative and insignificant effect on the interest in using QRIS, the benefit variable has a positive and significant effect on the interest in using QRIS, the risk variable has a negative and insignificant effect on the interest in using QRIS. While the test results (f) of the simultaneous variables of knowledge, benefits and risks have an influence on the interest in using the Quick Response Indonesian Standard (QRIS).